The regularity of the change in the coefficient of friction of the coupling of "shaft-sleeve" parts using polymeric materials - Aulin, V.V.; Lysenko, S.V.; Hrynkiv, A.V.; Tykhyi, A.A.; Kuzyk, O.V.; Livitskyi, O.M. (Problems of Tribology, 2023)
For the conjugation of samples and parts of the "shaft-sleeve" type, from the theoretical and experimental points of view, the laws of the change of the coefficient of friction for the combined polymer-metal material and coating were considered. Based on the law of energy conservation and transformation in the friction zone, expressions for estimating friction coefficients for polymer coatings and combined polymer-metal materials were obtained, taking into account the properties of thermal conductivity and elasticity and the geometric dimensions of the polymer and metal components. The consistency of the patterns of change in the friction coefficient has been clarified in tribocouplings of samples and parts from load and sliding speed in modes without lubrication and at extreme friction. To substantiate the effective operation of tribocoupling of parts made of combined polymer-metal materials, a criterion was introduced - the coefficient of wear, which is used to evaluate the tribological efficiency. It is shown that the obtained experimental results do not contradict the theoretical justification